Constrained Control of non-Holonomic Mobile Manipulator by Explicit Reference Governor - Luiz, A. B. H.; Ebrahim, S. E.; Edson, R. P. (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2021)
Mobile manipulators have advantages over fixed manipulators in terms of mobility, work-space, and utility. However, because it is a nonlinear system with complex operations, several types of controllers are explored for the movement and control of the system. Nevertheless, few articles address constrained motion. This paper presents a constrained control strategy known as Explicit Reference Governor (ERG) applied to a nonholonomic mobile manipulator with two degrees of freedom (2-DOF) guidance problem subject to constraints in work-space and singularities. In contrast to other solutions for the control with restriction problem, the ERG provides low-cost computation solutions applied directly to the controlled system, which are interesting for robotic systems whose computational and energetic resources are limited. Given a pre-stabilized system, the ERG generates a modified reference to the system conducted to the desired one respecting the restriction. For the proposed application, it is necessary the model and pre-stabilization of the mobile manipulator. For simplicity, we control the system in its work-space with inverse dynamics control (IDC). We study and prove the effectiveness of the proposition with simulation results considering restrictions in the robot work-space.